Nutritional Analysis And Hazard Risk Assessments Of Selected Aquaculture Species In Penang Focusing On Fish Oil Characteristics Of Golden Pompano (Trachinotus Blochii) - Arshad, Naufal (2024)
Aquaculture is a rapidly growing food production sector to alleviate global hunger, malnutrition, food security and nutrition deprivation. This study is aimed to explore a comprehensive spectrum of nutritional composition using aquaculture species. High commodity values aquaculture species in Penang, Malaysia were selected, and their nutritional quantification and health risk estimation were assessed. The study also extracted fish oil from the aquaculture products and evaluating their biological activities. Six marine aquaculture species, namely bigeye trevally, golden pompano, golden snapper, grouper, red snapper, and seabass were studied extensively. All cultured species contained adequate protein and lipid content, ranging from 21.1 to 26.9%, and 0.4 to 10.7%, respectively. Essential amino acid (EAA) to the total amino acid ratio (TAA) of culture species was comparable to the FAO reference values (50%), with leucine and lysine demonstrated the most important EAA. Fatty acid profiling showed that seabass and grouper were rich in polyunsaturated fatty acids (PUFAs), particularly docosahexaenoic acid (DHA). Golden pompano and red snapper contained the greatest values of riboflavin and pyridoxine. The nutritional quality indices indicated that the cultured species were within the permissible ratios (<1) for both atherogenic and thrombogenic indices. All cultured species potentially contributed more than 10% of protein, vitamin D3, and B2, K, Mg, P, and less than 1% of vitamin A, E, B6, Na, and Ca for both the adult and children populations in Malaysia.